Factors Affecting the Production of Banggai Sweet Potato in Banggai Laut Regency - Ruslan A Zaenuddin; Yuni Rustiawati; Helga Basai (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2022)
Banggai sweet potato is a local food crop typical of the Banggai Laut area, which is currently experiencing a decline in production, so there is a need for an appropriate strategy to increase its production. This study aims to analyze the factors and their significance to the production of sweet potato production in Banggai Selatan District, Banggai Laut Regency. The research was conducted from June to August 2022 in Malino Village, South Banggai District, Banggai Laut Regency. The data collected consisted of primary data, namely direct interviews with respondents and secondary data obtained from the Banggai Laut District Agriculture Office. Data were analyzed with multiple linear regression formulas, F test, t-test, coefficient of determination, and correlation coefficient using SPSS 16.0 software. The results showed that based on the F test, the variable capital, labor and the number of seeds together significantly affected Banggai sweet potato production. The significance value of the capital variable is 0.218, and the number of seeds is 0.796, which is greater than α 0.05, which means that the capital variable and the number of seeds have no significant effect on Banggai sweet potato production. The labor significance value of 0.000 is less than α 0.01, meaning that the labor variable significantly affects Banggai sweet potato production. The correlation coefficient value of 0.864 means that the variables of capital, labor, and number of seeds strongly relate to Banggai sweet potato production. The coefficient of determination is 0.747, meaning that 74.7% of the variable capital, labor, and the number of seeds affect the Banggai sweet potato production variable. In comparison, the remaining 25.3% of Banggai sweet potato production is influenced by other variables not present in the model. Labor is an important factor that needs to be considered in the Banggai sweet potato farming process